Naphthalimide-functionalized bisphosphonates for fluorescence detection of calcification in soft tissues - Oshchepkov, Aleksandr; Oshchepkov, Maxim; Pavlova, Galina; Ryabova, Anastasiya; Kamagurov, Semen; Tkachenko, Sergei; Frolova, Svetlana; Redchuk, Anatoly; Popov, Konstantin; Kataev, Evgeny (Sensors and Actuators B-Chemical, 2020)
Novel naphthalimide-functionalized bisphosphonates with different spacer length have been designed and synthesized. The spectroscopic properties, dissociation constants and complexation behavior with calcium(II) have been studied in aqueous solution. It has been shown that the length of the spacer has a dramatic effect on the fluorescence, Ca2+ binding properties and solubility of Ca2+ complexes in aqueous solution. New fluorescent bisphosphonates have been found to provide a perfect contrasting of inorganic industrial fouling (barite) and human tissue calcification (hydroxyapatite). The affinity of the fluorescent bisphosphonates for the bone matrix in the presence of human fibroblast cells has been tested in vitro with hydroxyapatite crystals imitated the human bone. Microscopic fluorescence analysis has demonstrated that fluorescent bisphosphonates are able to bind efficiently and selectively to the hydroxyapatite in the presence of human fibroblast cells.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Antiscalants; Bisphosphonates; Fluorescent dye; Naphthalimide; Soft tissue calcification